2016
DOI: 10.3390/toxins8110313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Compounds Blocking the Colony Pigmentation on the Aflatoxin B1 Production by Aspergillus flavus

Abstract: Aflatoxins and melanins are the products of a polyketide biosynthesis. In this study, the search of potential inhibitors of the aflatoxin B1 (AFB1) biosynthesis was performed among compounds blocking the pigmentation in fungi. Four compounds—three natural (thymol, 3-hydroxybenzaldehyde, compactin) and one synthetic (fluconazole)—were examined for their ability to block the pigmentation and AFB1 production in Aspergillus flavus. All compounds inhibited the mycelium pigmentation of a fungus growing on solid medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
11
0
3
Order By: Relevance
“…These compounds cause mycotoxicoses in animals and are carcinogens and/or allergens for humans, while their producers are among nosocomial infections that are especially dangerous for immunodeficient patients. Earlier we showed that 6-DMM suppressed the biosynthesis of a polyketide aflatoxin B1 in a toxigenic Aspergillus flavus [45]. In this regard, there is a suggestion that the antifungal effect of 6-DMM may be accompanied by the inhibition of the biosynthesis of toxins in other toxigenic fungi.…”
Section: Discussionmentioning
confidence: 79%
“…These compounds cause mycotoxicoses in animals and are carcinogens and/or allergens for humans, while their producers are among nosocomial infections that are especially dangerous for immunodeficient patients. Earlier we showed that 6-DMM suppressed the biosynthesis of a polyketide aflatoxin B1 in a toxigenic Aspergillus flavus [45]. In this regard, there is a suggestion that the antifungal effect of 6-DMM may be accompanied by the inhibition of the biosynthesis of toxins in other toxigenic fungi.…”
Section: Discussionmentioning
confidence: 79%
“…However, further investigations are necessary to confirm the PR-ZHD promise for the application on ZEN-polluted forage wheat with the purpose of simultaneous decontamination and improving the availability of feed nutritional components. Another possible way to provide a highly effective biological protection of agricultural feedstock from contamination is a combination of mycotoxin-degrading enzyme preparations and the natural inhibitors of the toxigenesis [50]. Such preparations might be used for providing an additional feed decontamination in those cases when an inhibitor incompletely suppresses the biosynthesis of mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that ST and melanin biosynthesis pathways could be linked, either directly or indirectly. Referring to the structural similarities between the first stable intermediate of melanin biosynthesis and AF biosynthesis in Aspergillus species, some researchers proposed that AF and melanin biosynthetic pathway share common initial stages, later the polyketide biosynthetic chain may branch toward different pathways resulting in the production of either AF or melanin (Brown and Salvo, 1994;Dzhavakhiya et al, 2016).…”
Section: Discussionmentioning
confidence: 99%